Do Insurance-mandated Precertification Criteria and Insurance Plan Type Determine the Utilization of Bariatric Surgery Among Individuals With Private Insurance?. Issue 11 (November 2020) - Gasoyan, Hamlet; Soans, Rohit; Ibrahim, Jennifer K.; Aaronson, William E.; Sarwer, David B.
Abstract : Background: Access to bariatric surgery is restricted by insurers in numerous ways, including by precertification criteria such as 3–6 months preoperative supervised medical weight management and documented 2-year weight history. Objectives: To investigate if there is an association between the aforementioned precertification criteria, insurance plan type, and the likelihood of undergoing bariatric surgery, after controlling for potential sociodemographic confounders. Research Design: The study was conducted using the Pennsylvania Health Care Cost Containment Council's data in 5 counties of Pennsylvania in 2016 and records of preoperative insurance requirements maintained by the Temple University Bariatric Surgery Program. Privately insured bariatric surgery patients and individuals who met the eligibility criteria but did not undergo surgery were identified and 1:1 matched by sex, race, age group, and zip code (n=1054). Univariate tests and logistic regression analysis were utilized for data analysis. Results: The insurance requirement for 3–6 months preoperative supervised medical weight management was associated with smaller odds of undergoing surgery [odds ratio (OR)=0.459; 95% confidence interval (CI), 0.253–0.832; P =0.010], after controlling for insurance plan type and the requirement for documented weight history. Preferred provider organization (OR=1.422; 95% CI, 1.063–1.902; P =0.018) and fee-for-service (OR=1.447; 95% CI, 1.021–2.050; P =0.038) plans were associated with greater odds of undergoing surgery, compared with health maintenance organization plans, after controlling for the studied precertification requirements. The documented weight history requirement was not a significant predictor of the odds of undergoing surgery ( P =0.132). Conclusions: There is a need for consideration of insurance benefits design as a determinant of access to bariatric surgery.